Development of Tracking Technique for the Short Term Rainfall Field Forecasting. (2016) - Kim, Tae-Jeong; Kwon, Hyun-Han
Abstract: Recently, rapid change awareness of spatial and temporal variability of rainfall that change is an attempt to prevent disasters such as flash floods due to heavy rainfall. Rainfall is one of the important input factors of hydrological models. But rainfall events such as heavy rains and a typhoon that occurs frequency due to global climate change are difficult to forecast. Weather radar rainfall data has been recognized for making a valuable contribution to short term flood forecasting and management over the past decades. There are several advantages to better monitoring rainfall in ungauged area compared to ground based rainfall gauges with which spatial patterns of the rainfall are not effectively identified. Hence, this study aims to develop a new scheme to forecast spatial and temporal rainfall field. The proposed model was based on an advection scheme to track wind patterns and velocity. The results showed a promising forecasting skill with quantitative and qualitative measures. It was confirmed that the forecasted rainfall may be effectively used an input data for a distributed hydrological model. In other words, the hydrological model in conjunction with high-resolution flash flood forecasting system is expected to be available.